Phylogenetic relationships of Iranian infectious hematopoietic necrosis virus of rainbow trout (Oncorhynchus mykiss) based on the glycoprotein gene - Adel, Milad; Amiri, Alireza Babaalian; Dadar, Maryam; Breyta, Rachel; Kurath, Gael; Laktarashi, Bahram; Ghajari, Amrolah (Archives of virology, 2016)
Infectious hematopoietic necrosis virus (IHNV), a member of family Rhabdoviridae and genus Novirhabdoviridae, causes a highly lethal disease of salmon and trout. In Iran IHNV was first detected in 2001 on farms rearing rainbow trout (Oncorhynchus mykiss). To evaluate the genetic relationships of IHNV from northern and western Iran, the sequences of a 651-nt region of the glycoprotein gene were determined for two Iranian isolates. These sequences were analyzed to evaluate their genetic relatedness to worldwide isolates representing the five known genogroups of IHNV. Iranian isolates were most closely related to European isolates within the genogroup E rather than those of North American genogroups U, M and L, or the Asian genogroup J. It appears that Iranian IHNV was most likely introduced to Iran from a source in Europe by the movement of contaminated fish eggs.